Predictive significance of Charcot‐Leyden crystal structures for nasal polyp recurrence. Issue 11 (22nd November 2022) - Chen, Wenyi; Bai, Yurong; Kong, Weifeng; Luo, Xin; Zeng, Yinhui; Chen, Jingyuan; Wang, Xinyue; Wu, Qingwu; Chaudhuri, Shuvam; Chen, Jianning; Yang, Qintai; Zhang, Yana
Abstract: Background: Charcot‐Leyden crystals (CLCs) are recognized to be classic hallmarks of eosinophilic inflammation. Both protein and mRNA levels of CLC in nasal secretions and nasal brushing samples have been associated with nasal polyp recurrence. However, whether the crystalline CLC structures in nasal tissue could serve as an effective biomarker to predict polyp recurrence remains unclear. Methods: A total of 110 patients with chronic rhinosinusitis with nasal polyps (CRSwNP) completing the postoperative follow‐up over a period of 24 months were recruited. Hematoxylin and eosin staining was employed for CLCs identification. The predictive factors for polyp recurrence were determined by binary logistic regression analysis. Results: Thirty three (30.00%) patients developed recurrence during a 24‐month postoperative follow‐up, in which 84.85% (28/33) patients had crystalline CLC structures. Logistic regression analysis showed that crystalline CLC structure in nasal tissues is predictive of polyp recurrence. Youden index demonstrated crystalline CLC structure higher than 1 per high power field can predict postoperative polyp recurrence with 84.80% sensitivity and 98.70% specificity. Conclusions: The crystalline CLC structures in nasal tissues may serve as an easy‐counting and promising biomarker to predict CRSwNP recurrence.